The War of 1812 : a forgotten conflict - Hickey, Donald R., 1944- (University of Illinois Press, 2012)
"This comprehensive and authoritative history of the War of 1812, thoroughly revised for the 200th anniversary of the historic conflict, is a myth-shattering study that will inform and entertain students, historians, and general readers alike. Donald R. Hickey explores the military, diplomatic, and domestic history of our second war with Great Britain, bringing the study up to date with recent scholarship on all aspects of the war, from the Gulf of Mexico to Canada. With additional information on military operations such as the importance of logistics and the use and capabilities of weaponry, The War of 1812: A Forgotten Conflict, Bicentennial Edition explains how the war promoted American nationalism and manifest destiny, stimulated peacetime defense spending, and enhanced America's reputation abroad. Hickey also concludes that the war sparked bloody conflicts between pro-war Republican and anti-war Federalist neighbors, dealt a crippling blow to American Indians, and solidified the United States's antipathy toward the British."--Project Muse.